Work–family conflict and the performance of women-owned businesses: The role of work–family centrality - Dapula, Chumasande (University of the Free State, 2022)
Women entrepreneurs have been internationally recognised as being major contributors to job creation, poverty alleviation, and economic growth in their respective environments across the world. The main aim of this study was to investigate the impact of work–family conflict on the performance of women-owned businesses in Mangaung Metropolitan Municipality (Bloemfontein, Botshabelo, and ThabaNchu) and the impact work–family centrality has on these relationships. The study explored whether work–family centrality can explain the differences in performance amongst women entrepreneurs based on the type of work–family conflict and family–work conflict they experienced. The study made use of quantitative research through the distribution of 350 questionnaires to women entrepreneurs in the Free State from the Mangaung Metropolitan Municipality (Bloemfontein, Botshabelo, and Thaba ‘Nchu). Findings in the study provided insight on the impact of work–family conflict and family–work conflict on the performance of women entrepreneurs and the role work–family centrality has on this association. The study found that work–family centrality had no moderating effect on the work–family conflict-performance relationship. Further, it was established that high work–family conflict has a positive impact on the performance of women-owned business. The developing context has not received much attention from research; therefore, this study aids in improving the understanding of the context within which women entrepreneurs operate in South Africa and assists in bringing forth new insights on women entrepreneurs and thus provides alternative explanations to women entrepreneurs’ differences in performance. Further, the study contributes to understanding the employer’s perspective better to contribute to the existing research on work–family centrality and enhance the performance of businesses owned by women.
Dissertation (M.Com.(Business Management))--University of the Free State, 2022